(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Karakalpak poetry is the leading genre of our literature. In recent years, our poetry has grown fuller and more inspired, achieving considerable success in highlighting the dedication of our people to portraying the scale of its time. Scholar S. Akhmetov described the achievements of Karakalpak poetry in the 1970s, stating that by the 1980s, Karakalpak poetry had reached its peak. Compared to the present time, poetry has deepened in terms of content and has begun to manifest itself in the choice of form.